Multidrug resistance and inappropriate empiric therapy as predictors of hospital stay in diabetic foot infections - Lana Zuriegat; Rania Itani; Khawla Abu Hammour; Rana Abu-Farha (PLoS ONE, 2026)
Objectives This study explored the causative pathogens, resistance patterns, and treatment appropriateness for diabetic foot infections (DFI) at a tertiary care center in Jordan. Methods A retrospective review was conducted on 234 patients diagnosed with DFIs at a tertiary care center in Jordan. Data collected included patient demographics, diabetes history, infection severity, culture results, and antibiotic treatment details. Bacterial isolates were classified as multidrug-resistant (MDR) or non-MDR based on standard definitions. Therapy was considered appropriate if at least one antibiotic given within the first 48 hours of admission covered all identified pathogens and was administered with the correct dosage, formulation, and route. Statistical analyses examined the relationship between resistance patterns, treatment adequacy, and hospital stay duration. Results The most frequently isolated bacterium was Staphylococcus aureus , identified in 117 cases (50.0%), including MRSA (n = 46, 19.6%) and MSSA (n = 71, 30.3%). This was followed by Escherichia coli in 33 cases (14.1%) and Pseudomonas aeruginosa in 32 cases (13.7%). MDR organisms accounted for 152 infections (65%). Empiric therapy was deemed appropriate in 111 patients (47.4%), inappropriate in 74 (31.6%), and not assessable due to missing data in 49 (20.9%). Following culture and susceptibility results, antibiotics in 87 cases (37.2%) remained unchanged. In multivariate analysis, only infection severity was significantly associated with prolonged hospitalization (β = −0.161, P = 0.034). Conclusion MDR organisms were common in DFIs but not significantly associated with prolonged hospitalization. Infection severity was the key predictor of length of stay. These findings highlight the importance of early infection assessment, appropriate empirical therapy based on local resistance patterns, and robust antibiotic stewardship.